Game Online Mengganggu Konsentrasi Dan Perilaku Belajar Siswa Sekolah Dasar Di Lenek - Khaerul Azmi; Badarudin Badarudin; Muhamad Juaini (Educatio, 2025)
Abstract This research aims to examine the impact of online games on the concentration and learning behavior of elementary school students in Lenek. In the digital era, online games have become a widespread phenomenon among children, including elementary school students. Excessive use of online games is suspected to disrupt concentration and alter students' learning behavior. This study uses a qualitative method with a case study approach. Data were collected through observation, interviews, and document analysis. The research results indicate that online games have a significant influence on the concentration and learning behavior of elementary school students. Negative impacts found include decreased learning focus, lack of learning motivation, and less positive behavioral changes. This research concludes that more attention is needed from parents, teachers, and schools in supervising the use of online games among elementary school students.